Pengembangan Sistem Informasi Sumber Daya Manusia Rumah Sakit - Selvia Magdalena; Vip Paramarta; Prayudha Adhi Laksono; Rifai Setiyo Gusti (Jurnal Anestesi, 2023)
In the current era of globalization, the rapid development of information technology has penetrated into various sectors including health. The development model of information systems and reports has been computerized. The system, which was originally done manually, is now shifting towards the automation process. Therefore, in making information, a system is needed that can make precise and accurate information. Management information systems need to be defined in more detail to obtain more specific information in hospitals. Hospital human resource information systems provide information to all managers in the hospital. Hospitals can apply management information systems in resource management, especially in job vacancy data, applicant data, permanent employee appointment data, employee data, retirement data, resignation data, employee reward and punishment history data, attendance data, leave data, and position change data to improve effective and efficient human resource performance.